The Effect of Fans' Perceptions of Psychological Commitment to their Team on Respect and Hatred towards Opponents - Hatice Deveci Şirin; Erkan Faruk Şirin (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to determine the effect of fans' perceptions of psychological commitment to their teams on their respect and hatred towards opponents. The study group consists of 400 fans of clubs called as the Big Three (Beşiktaş, Fenerbahçe and Galatasaray) residing in Konya during the 2021-2022 football season. In the study in which survey and relational survey models were used, Personal Information Form, Fan Psychological Commitment Scale and Respect for Opposite Opinions and Self-Control Scale in Sports were used to collect data. As a result of the study, it was found that personal identity, resource cost and social obligation, which are the sub-dimensions of psychological commitment to the team, increase hatred towards the opponent, while affective commitment decreases hatred towards the opponent. In the Multiple Regression Analysis conducted to examine the extent to which psychological commitment to the team predicts hatred towards the opponent, it was found that 39% of hatred towards opponent was explained. In addition, it was found that regional tribalism, one of the sub-dimensions of psychological commitment to the team, increased the respect towards the opponent, while social obligation decreased the respect towards the opponent. In the Multiple Regression Analysis conducted to examine the extent to which psychological commitment to the team predicts respect towards opponent, it was seen that 8% of respect towards opponent was explained. It is considered that the findings of the study will contribute to the development of policies to increase sportsmanship and fairplay behaviours of fans and to prevent aggression.